Combining legal epidemiology and implementation science to improve global access to medicines: challenges and opportunities - Lane, Jeff; Stergachis, Andy (Frontiers in Health Services, 2024)
Laws and policies affecting access to medicines have been in the global health spotlight for decades, yet our understanding of their effects remains substantially underdeveloped. The emerging field of legal epidemiology combined with the methods of implementation science presents an opportunity to help address this gap. Legal epidemiology refers to the scientific study and deployment of law as a factor in the cause, distribution, and prevention of disease and injury in a population. Legal epidemiology studies consist of a systematic collection and coding of laws and policies relating to a particular topic. Quasi-experimental or observational research methods can then be applied to take advantage of natural experiments resulting from heterogenous adoption and/or implementation of laws and policies. Often legal epidemiology studies fail to account for heterogenous law implementation processes, presenting a need and opportunity to integrate implementation science methods. Researchers may face challenges in integrating these methods for access to medicines studies, including data access issues and a complex legal and implementation environment. Yet, the opportunities presented by increasingly transparent legal environments, improved monitoring of medicine availability, universal health coverage expansion, and electronic health and insurance records integration may facilitate overcoming these challenges. Improved collaboration and communication between researchers, health authorities, manufacturers, and health providers from public and private sectors will be critical. In spite of the challenges, combining the fields of legal epidemiology and implementation science may present an important strategy toward creating a legal and policy environment that supports global and equitable access to medicines.